CO2 geo-sequestration modeling study for contact angle estimation in ternary systems of brine, CO2, and mineral. (10th February 2021) - Sun, Xinpo; Bi, Yuzhang; Guo, Yi; Ghadiri, Mahdi; Mohammadinia, Samira
Highlights: Novel ELM and GTB models are used for estimating brine/CO2/mineral contact angles. Accuracy of models are proved for simulation of CO2/brine wettability on minerals. Outlier detection and sensitivity analyses are used for further investigation.